Eating behavior and quality of life in high school pupils in Lviv - S.L. Nyankovskyy; O.R. Sadova (Zaslavsky O.Yu., 2018)
Background. The negative dynamics of the health of the children population needs to increase attention to this problem, first of all - to provide an effective preventive component of medical care. Analyzing the reasons for the negative dynamics of the health status indicators in Ukrainian children, it is necessary to pay attention to the way of life, which occupies the leading position in the structure of the factors of influence on health. In view of this, we analyzed the peculiarities of lifestyle, eating behavior of high school students and their impact on the main quality of life parameters. Materials and methods. To achieve the goal, we studied lifestyle and eating behavior in 80 healthy high school pupils aged 14-17 years using a questionnaire containing questions about the family anamnesis, living conditions, day regime and nutrition. For the evaluation of the quality of life, we used international questionnaire MOS SF-36. Results. Eating behavior analysis has showed that 45 % of high school pupils take products of industrial production containing meat everyday. Fish plates occur in everyday diet significantly rare than meat ones, only in 13.75 % (p < 0.05). 16.25 % of children do not have fish plates at all. Dairy foods and milk are signed in everyday diet less than in a half of the surveyed children (35 %). We found a high percentage of adolescents who drink low-alcohol drinks (15 %). We revealed that 45 % of adolescents use the computer or watch TV more than 3 hours per day, only 22 % of examinees spend their time outside on fresh air more than 2 hours per day. The quality of life data revealed authentically higher indexes by the scale of viability in children spending outdoor more than 2 hours. We determined that in children who have proper meal every day, there are sufficiently higher indexes of community relief, value determined by the scale of psychological health and by the scale of viability (p < 0.05). We noted the sufficient decrease of viability index in group of children using computer for a long time (3 hours per day and more). In children go in for sport, there are significantly higher quality of life indexes determined by the scale of psychological health and by the scale of general health. Besides, in older children sleeping 8 hours per night, a sufficiently higher emotional stability is noticed determined by the scale of role-emotional functioning (p < 0.05). Conclusions. The diet of high school pupils does not meet the established standards. This may be a risk factor for gastroduodenal pathology in the future, and therefore requires systematic correction. In addition to rational nutrition, factors affecting the health status and the psycho-emotional status of high school pupils are controlled physical activity, regular outdoor exercise and limited use of the computer. The method of assessing the quality of life is a simple and informative mean for comprehensive study of the health status of high school pupils and can be recommended for widespread use in pediatrics.